Peran Islam dalam Dinamika Politik Indonesia dari Kesultanan hingga Era Reformasi - Raudatul Husnah (PT Inovasi Penelitian Terpadu, 2026)
This article examines how Islam played a role in Indonesian political dynamics from the sultanate era to the Reformation. Through the lens of historical methods, this research explains that since the beginning, Islam has been an important factor in the legitimacy of government and power, as seen in the Demak and Aceh sultanates. Organizations such as the Sarekat Islam, founded in the early 20th century, played a significant role in combating colonialism. The debate over Islam's role in the state after independence became more complex, particularly to the Jakarta Charter, which recommended the implementation of Islamic law. Although Islam's political role was limited during the New Order, organizations such as Nahdlatul Ulama (NU) and Muhammadiyah remained active in social and educational fields. During the Reformation era, Islamic parties such as the Prosperous Justice Party (PKS) and the United Development Party (PPP) emerged, seeking to integrate Islamic values into the democratic system. However, the challenges of pluralism and radicalism created tensions in the application of Islamic principles. In this context, NU and Muhammadiyah served as instruments of moderation and promoted tolerance and harmony between different communities. Through this approach, Islam serves not only as a religion but also as a key pillar for building an inclusive and stable democracy in Indonesia.